Reformulación del principio de antropocentrismo ambiental (2016)
The main international declarations of environmental principles have evolved the principles of sustainable development, prevention, precaution, polluter pays , sovereignty of natural resources, transboundary harm , among others; However , despite such progress , there is a lag of a principle that is clearly in such statements, the environmental anthropocentrism, a concept that has been largely misunderstood to be understood as a utilitarian principle and overexploitation of natural resources ; However , this principle actually contains a close relationship with one of the most important principles in our legal system , the human dignity because if we understand the anthropocentrism as a stream will defend the importance of male supremacy or above else, then any infringement and impairment suffered by the human species violates this mandate